Naturally occurring germline and tumor-associated mutations within the ATP-binding motifs of PTEN lead to oxidative damage of DNA associated with decreased nuclear p53 - He, Xin (Oxford University Press, 2011)
Somatic and germline mutations in PTEN (phosphatase and tensin homolog deleted on chromosome 10) are found in sporadic cancers and Cowden syndrome patients, respectively. Recent identification of naturally occurring cancer and germline mutations within the ATP-binding motifs of PTEN (heretofore referred to as PTEN ATP-binding mutations) has revealed that these mutations disrupted the subcellular localization and tumor-suppressor activity of PTEN. However, very little is known about the underlying mechanisms of PTEN ATP-binding mutations in tumorigenesis. Here we show that these mutations impair PTEN's function both qualitatively and quantitatively. On the one hand, PTEN ATP-binding mutants lose their phosphatase activity and the effect of downregulation of cyclin D1. On the other, the mislocalized mutant PTEN results in a significantly decreased nuclear p53 protein level and transcriptional activity, enhanced production of reactive oxygen species, induction of Cu/Zn superoxide dismutase as well as dramatically increased DNA double-strand breaks (DSBs). When compared with wild-type PTEN, the ATP-binding mutant PTEN has reduced half-life in vitro and decreased protein expression levels in vivo. Our data, thus, reveal a novel mechanism of tumorigenesis in patients with germline or somatic mutations affecting PTEN ATP-binding motifs, i.e. qualitative and quantitative impairment of PTEN due to the loss of its phosphatase activity, and nuclear mislocalization, resulting in rapid PTEN protein degradation, suppression of p53-mediated transcriptional activity, loss of protection against oxidative stress as well as accumulation of spontaneous DNA DSBs.